Design of an MSME Information System for Via Fresh Vegetables using the Unified Process Method - Satria Satria; Ikka Novia Wijayanti (Universitas Wahid Hasyim, 2026)
Technology plays a crucial role in facilitating human activities, including in the agribusiness sector. Vegetables, as a primary food commodity, require a fast and accurate sales system to meet consumer demands. The Via Fresh Vegetables store still applies conventional sales methods, resulting in suboptimal sales management and customer service. The purpose of this study is to develop a web-based online vegetable sales information system that can assist the store in improving operational efficiency, information accuracy, and expanding its marketing reach. This study uses the Unified Process method, which applies iterative and incremental stages to understand requirements, design, build, and test the system repeatedly. This approach was chosen because it can produce a system that better meets user needs. The result of this research is a web-based sales information system that provides features such as product management, online ordering, transaction history, and customer management. The developed system can help Via Fresh Vegetables improve the effectiveness of its sales process, accelerate services, and provide more accurate information access for customers.